The Future Will Be Better Tomorrow. (29th June 2017) - Morgan, Robert F.
Abstract : It was 2012 in Singapore. There I saw a young boy in a mall wearing this hopeful T-shirt message: " The future will be better tomorrow. " This paradox of incidental wisdom suggests that our future path can be changed and we are the artists.